Implementasi Algoritma Rivest Shamir Adleman Untuk Keamanan Pesan Teks - Haggy Sandy Prayogy; Indra Kanedi; Devi Sartika (UNIVED Press, 2025)
Security is a set of procedures, steps, and policies to prevent and monitor unauthorized access, problem solving, disclosure, and disruption of computer data communication. Data or message security can be achieved using cryptography. Cryptography is an important component for communication and information transmission through security services. Cryptography is both an art and a science that produces secret messages. One cryptographic method that can be utilized is RSA method. RSA is an asymmetric cryptographic method that operates in block mode and requires two different keys for the encryption and decryption processes. The advantage of this algorithm is that its difficulty lies in factoring non-prime numbers into their prime factors. The results of the tests conducted show that RSA algorithm can provide additional security for files by using different keys during the encryption and decryption processes. This is because the text data owned by the user will be encrypted and replaced with a series of numbers that do not represent the content of the original data.